Menguak Budaya Matrilineal dalam Cerpen “Gadis Terindah” - Wahyuni, Dessy (Paradigma: Jurnal Kajian Budaya, 2017)
Matrilineal kinship system is adopted by the Minangkabau society. In fact, the system that follows the maternal lineage turns out to cause inner conflict for the people. Through a short story titled “Gadis Terindah”), Gus tf Sakai as the author tried to express this inner conflict. In this matrilineal culture, there is a necessity for men to leave their hometown, known as migrating. After being successful as migrating people, they have to return to their hometown, take their wealth to accumulate the wealth of people there by marrying a Minang girl. Inner conflict that developed by the author through a fictional character in the short story is expressed by applying a pragmatic approach to the theory of semiotics. Signs given by the author are examined by using text content analysis method. Thus, it is found that in the tradition of matrilineal culture, migrating, inheritance systems and matchmaking have been arranged. However, in fact, the system that has been organized remains conflict for its people.